Omega-3 Fatty Acid Supplementation Improves Endothelial Function in Primary Antiphospholipid Syndrome: A Small-Scale Randomized Double-Blind Placebo-Controlled Trial - Felau, Sheylla M.; Sales, Lucas P.; Solis, Marina Y.; Hayashi, Ana Paula; Roschel, Hamilton; Sá-Pinto, Ana Lúcia; Andrade, Danieli Castro Oliveira De; Katayama, Keyla Y.; Irigoyen, Maria Claudia; Consolim-Colombo, Fernanda; Bonfa, Eloisa; Gualano, Bruno; et al. (Frontiers in Immunology, 2018)
Endothelial cells are thought to play a central role in the pathogenesis of Antiphospholipid Syndrome (APS). Omega-3 polyunsaturated fatty acid (n-3 PUFA) supplementation has been shown to improve endothelial function in a number of diseases; thus it could be of high clinical relevance in APS. The aim of this study was to evaluate the efficacy of n-3 PUFA supplementation on endothelial function (primary outcome) of patients with primary APS (PAPS). A 16-week randomized clinical trial was conducted with 22 adult women with PAPS. Patients were randomly assigned (1:1) to receive placebo (PL, n=11) or n-3 PUFA (ω-3, n=11) supplementation. Before (Pre) and after (Post) 16 weeks of the intervention patients were assessed for endothelial function (peripheral artery tonometry) (primary outcome). Patients were also assessed for systemic markers of endothelial cell activation, inflammatory markers, dietary intake, international normalized ratio [INR]), and adverse effects. At Post, ω-3 group presented significant increases in endothelial function estimates reactive hyperemia index (RHI) and logarithmic transformation of RHI (LnRHI) when compared with PL (+13% vs. -12%, p=0.06, ES=0.9; and +23% vs. -22%, p=0.02, ES=1.0). No changes were observed for e-selectin, VCAM-1 and fibrinogen levels (p>0.05). Additionally, ω-3 group showed decreased circulating levels of IL-10 (-4% vs. +45%, p=0.04, ES=-0.9) and TNF (-13% vs. +0.3%, p=0.04, ES=-0.95) and a tendency towards a lower ICAM-1 response (+3% vs. +48%, p=0.1, ES=-0.7) at Post when compared with PL. No changes in dietary intake, INR or self-reported adverse effects were observed. In conclusion, 16 weeks of n-3 PUFA supplementation improved endothelial function in patients with well-controlled PAPS. These results support a role of n-3 PUFA supplementation as an adjuvant therapy in APS. Registered at clinicaltrial.gov as NCT01956188.